2007
DOI: 10.1002/ajmg.a.31558
|View full text |Cite
|
Sign up to set email alerts
|

Skin changes in oculo‐dento‐digital dysplasia are correlated with C‐terminal truncations of connexin 43

Abstract: Oculo-dento-digital dysplasia (ODDD, OMIM no.164210) is a pleiotropic disorder caused by mutations in the GJA1 gene that codes for the gap junction protein connexin 43. While the gene is highly expressed in skin, ODDD is usually not associated with skin symptoms. We recently described a family with ODDD and palmoplantar keratoderma. Interestingly, mutation carriers had a novel dinucleotide deletion in the GJA1 gene that resulted in truncation of part of the C-terminus. We speculated, that truncation of the C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 7 publications
0
40
0
1
Order By: Relevance
“…Although ODDD patients are usually not affected with skin symptoms, the fs260 mutation has been reported to be associated with palmoplantar keratoderma (van Steensel et al, 2005). More recently, it has been shown that skin changes in ODDD are correlated with Cterminal truncations of Cx43 (Vreeburg et al, 2007). Together, these data suggest that the association of Cx43 with Cav-1 in keratinocytes might play a functional role during epidermal differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…Although ODDD patients are usually not affected with skin symptoms, the fs260 mutation has been reported to be associated with palmoplantar keratoderma (van Steensel et al, 2005). More recently, it has been shown that skin changes in ODDD are correlated with Cterminal truncations of Cx43 (Vreeburg et al, 2007). Together, these data suggest that the association of Cx43 with Cav-1 in keratinocytes might play a functional role during epidermal differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…1A) (16) with the resulting disease outcome being classified as ODDD highlighted by developmental defects in the craniofacial bones around the eyes and nose, loss of enamel resulting in early destruction of the teeth, and lack of soft tissue separation of two or three digits (14). In addition to these commonly found developmental disorders, patients often exhibit an assortment of conditions that range broadly from neurological to cardiac disorders (14,(21)(22)(23)(24). It is possible that epigenetic effects may also contribute to these disease states.…”
Section: Autosomal Dominant Mutationsmentioning
confidence: 99%
“…It is possible that epigenetic effects may also contribute to these disease states. Interestingly, in cases in which the patient harbors a frameshift mutation (fs230 (24) or fs260 (25)) resulting in a gross deletion of the C terminus of Cx43, these individuals have an increased disease load of palmoplantar keratodermas or palmar hyperkeratosis not unlike what is found in some patients harboring dominant GJB2 mutations. The fact that one point mutation in Cx43 (L11P) (26) has been associated with hyperkeratosis suggests that the added disease load in the skin is not restricted solely to the events linked to the C terminus of the molecule.…”
Section: Autosomal Dominant Mutationsmentioning
confidence: 99%
“…3). Interestingly, except for the two mutations mentioned above [146,150] [103] in a family with ODDD and an increased incidence of cardiac arrhythmias. Cx43 was markedly reduced in mutant hearts with preferential loss of phosphorylated forms of the protein, resulting in dysfunctional GJs.…”
Section: Cx43 and Oculodentodigital Dysplasiamentioning
confidence: 93%
“…The authors stated that this was the first reported mutation affecting the COOH-terminal tail and suggested that this particular mutation might explain the presence of skin symptoms. Vreeburg et al [150] reported another Dutch woman with ODDD and palmar hyperkeratosis with a 2-bp deletion in the Cx43 gene resulting in truncation of the protein and absence of a significant portion of the C-terminal domain. The findings suggested a genotype/ phenotype correlation between pronounced PPK and mutations that truncate the C terminus of Cx43.…”
Section: Cx43 and Oculodentodigital Dysplasiamentioning
confidence: 98%